Variable Speed Drives: Energy Saving and SCADA System - Sahlan, Shafishuhaza (International Journal of Integrated Engineering, 2017)
In this paper, implementation of variable speed drives (VSD) in a water treatment plant (WTP) and its capability in energy consumption reduction is presented. Conducted in Titi WTP, Negeri Sembilan, Malaysia, the project was run for four years, i.e. from early 2011 until the end of 2014. In the duration of four years, four VSDs are installed in the raw water pump house (RWPH) and treated water pump house (TWPH) of the plant with a power rating of 130kW and 260kW respectively. The electrical energy consumption of the plant before VSD installation was recorded as reference and a comprehensive supervisory control and data acquisition (SCADA) system was installed to remotely and automatically control the pump operation of the WTP. From The results obtained, it can be observed that, at the end of the four years, a saving of 26.64% and 24.58% for the energy consumption (kWh) and the overall cost (RM) respectively is achieved. Meanwhile, the payback period or the return on investment (ROI) period is calculated to be 3.4 years.